Elektronifikasi Permohonan Persetujuan Impor Dalam Mencegah Gratifikasi - Wahyudi, Ari; Lie, Gunardi; Sitabuan, Tundjung Herning; Neljeane, Jeane (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Corruption in its various types is an extraordinary crime, so extraordinary efforts are also needed (extraordinary enforcement), and extraordinary efforts are also needed to eradicate it (extraordinary measures). This study aims to analyse whether digital transformation (digitization) of import approval applications can prevent gratification practices that commonly occur in the administrative process of import approval applications if reviewed based on Government Regulation 29 of 2021 concerning Operators in the Trade Sector in the Prevention of Gratification. The type of research used in this proposal is normative juridical research. The approach used in this research is the statute approach. The results show that electronification of import approvals based on Government Regulation Number 29 of 2021 concerning organisers of the trade sector in the prevention of gratification is a brilliant breakthrough and very effective in preventing the practice of gratification. This is because Article 7 has offered a complicated technical mechanism for registering business licences in an integrated system, so this government regulation is considered effective because it offers a mechanism for registering business licences (including import approvals) electronically.